2020
DOI: 10.1177/0734282920951065
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Behavior Assessment System for Children-3 Behavioral and Emotional Screening System Student-Report Form among a Predominantly Latinx Elementary School Sample

Abstract: School-based universal screening for behavioral/emotional risk is a necessary first step in the identification of students who might need services within a behavioral response to intervention model. When choosing among the available screening measures, psychometric information such as reliability and validity of the scores is critical to inform such decisions. The purpose of the present study was to examine the reliability and validity of the Behavior Assessment System for Children (BASC)-3 Behavioral and Emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The test-retest reliability coefficients for the BASC-3 are high enough (α = 0.77-0.91) to support using the data for disability identification (Dever & Gaier, 2020). Research suggests that both direct testing (i.e., CELF-5) and parent/teaching rating scales (i.e., SRS-2) can be utilized for assessing receptive and expressive language in students with suspected AU (Nordahl-Hansen et al, 2014).…”
Section: Languagementioning
confidence: 92%
“…The test-retest reliability coefficients for the BASC-3 are high enough (α = 0.77-0.91) to support using the data for disability identification (Dever & Gaier, 2020). Research suggests that both direct testing (i.e., CELF-5) and parent/teaching rating scales (i.e., SRS-2) can be utilized for assessing receptive and expressive language in students with suspected AU (Nordahl-Hansen et al, 2014).…”
Section: Languagementioning
confidence: 92%
“…Higher vocational college (HVC) students face many academic competition and social adaptation challenges, and a good PR is a necessary condition for their academic success and healthy development. Research has shown that individuals with higher PR level have lower symptoms of depression and anxiety and have higher self-esteem and happiness [3][4][5][6] . Even though HVC students are inexperienced and lack the corresponding social skills and life experiences, they have to face all types of events in their lives independently.…”
Section: Introductionmentioning
confidence: 99%